Tissue- and cell-specific mitochondrial defect in Parkin-deficient mice. - Maria Damiano (PLoS ONE, 2014)
Loss of Parkin, encoded by PARK2 gene, is a major cause of autosomal recessive Parkinson's disease. In Drosophila and mammalian cell models Parkin has been shown in to play a role in various processes essential to maintenance of mitochondrial quality, including mitochondrial dynamics, biogenesis and degradation. However, the relevance of altered mitochondrial quality control mechanisms to neuronal survival in vivo is still under debate. We addressed this issue in the brain of PARK2-/- mice using an integrated mitochondrial evaluation, including analysis of respiration by polarography or by fluorescence, respiratory complexes activity by spectrophotometric assays, mitochondrial membrane potential by rhodamine 123 fluorescence, mitochondrial DNA content by real time PCR, and oxidative stress by total glutathione measurement, proteasome activity, SOD2 expression and proteins oxidative damage. Respiration rates were lowered in PARK2-/- brain with high resolution but not standard respirometry. This defect was specific to the striatum, where it was prominent in neurons but less severe in astrocytes. It was present in primary embryonic cells and did not worsen in vivo from 9 to 24 months of age. It was not associated with any respiratory complex defect, including complex I. Mitochondrial inner membrane potential in PARK2-/- mice was similar to that of wild-type mice but showed increased sensitivity to uncoupling with ageing in striatum. The presence of oxidative stress was suggested in the striatum by increased mitochondrial glutathione content and oxidative adducts but normal proteasome activity showed efficient compensation. SOD2 expression was increased only in the striatum of PARK2-/- mice at 24 months of age. Altogether our results show a tissue-specific mitochondrial defect, present early in life of PARK2-/- mice, mildly affecting respiration, without prominent impact on mitochondrial membrane potential, whose underlying mechanisms remain to be elucidated, as complex I defect and prominent oxidative damage were ruled out.